2019
DOI: 10.1007/s40093-019-00299-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving soil silicon and selected fertility status for rice production through rice-mill waste application in lowland sawah rice field of southeastern Nigeria

Abstract: Purpose Rice-mill wastes are generated in large amounts in Ishiagu, Ebonyi State, Nigeria. These wastes can potentially be utilized for rice production and in improving soil attributes. This study evaluated the effects of rice-mill wastes on soil chemical properties and rice yield in sawah rice management. Methods A sawah rice field in an inland valley of southeastern Nigeria was used in 2014 and 2015 cropping seasons for the study. Sawah refers to an Indo-Malaysian term for rice paddy. It involves the manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
1
10
0
2
Order By: Relevance
“…The highest amount of organic carbon and organic matter (2.00% and 3.46% respectively) were recorded in plot that had 5tonha -1 RHD and 3tonha -1 NPK, while their least values were obtained in plot that had only 5tonha -1 NPK. The observed rate of enhancement in soil organic carbon and organic matter could be attributed to the high content of organic carbon in the RHD as also observed by Nwaite et al [7]. This findings can be justified on the bases that while organic manures improve soil biology and organics at sustainable levels [29], mineral fertilizers use at consistent manner are known to destroy soil health especially soil organic matter [29].…”
Section: Effect Of Rice Husk Dust and Npk Fertilizer On Soil Chemicalsupporting
confidence: 70%
See 1 more Smart Citation
“…The highest amount of organic carbon and organic matter (2.00% and 3.46% respectively) were recorded in plot that had 5tonha -1 RHD and 3tonha -1 NPK, while their least values were obtained in plot that had only 5tonha -1 NPK. The observed rate of enhancement in soil organic carbon and organic matter could be attributed to the high content of organic carbon in the RHD as also observed by Nwaite et al [7]. This findings can be justified on the bases that while organic manures improve soil biology and organics at sustainable levels [29], mineral fertilizers use at consistent manner are known to destroy soil health especially soil organic matter [29].…”
Section: Effect Of Rice Husk Dust and Npk Fertilizer On Soil Chemicalsupporting
confidence: 70%
“…During rice refining processes, the husks are removed from grains. It is of little commercial value and because of its high silicon dioxide content; it is not useful to feed either human or cattle [7], but can be incorporated into the soil to enhance soil fertility and crop productivity. For example, organic modification of soil with rice husk was found effective in improving the nutrient status and thus increased the yield of many crops like cowpea and rice [6].…”
Section: Introductionmentioning
confidence: 99%
“…There was a built-up to an extent of 0.68 percent in available Si content of the soil when compared to the initial status even without its fertilization. This could be due to the reason that Si fertilizers increased the content of plantavailable Si compounds [24] in the soil. This was attributed to the possibility of sorption and desorption of silicate fertilizer under the wetland rice ecosystem of the present study.…”
Section: Effect Of Different Combinations Of N Nutrient Status Ofmentioning
confidence: 99%
“…What was still unclear on the general phenomenon of low Jatropha yield at younger ages has been made clearer through the improvement on soil fertility properties by the addition of RHD and NPK. The soil fertility enhancement potentials of rice husk dust in highly weathered acidity tropical soils have been reported by several authors [30] Azu et al [9] Nwaite, et al [31]. Jatropha cultivation traditionally receives minimal care in terms of soil fertility maintenance.…”
Section: Effect Of Rice Dusk Dust and Npk Fertilizer On The Number Ofmentioning
confidence: 99%
“…Thus, Omar et al [34] discovered significant increased in seed and oil quantity of Jatropha produced in soils treated with different rates of nitrogen and potassium fertilizers. Njoku et al [8] and Nwaite et al [31], in their separate studies observed improved soil fertility and corresponding plant response when rice husk dust was used as manure in ultisols of southeastern Nigeria.…”
Section: Effect Of Rice Husk Dust and Npk On The Weight Of Seeds Per mentioning
confidence: 99%